KETIDAKPATUHAN PEMERINTAH TERHADAP PUTUSAN PENGADILAN SEBAGAI IMPLIKASI PUTUSAN MAHKAMAH KONSTITUSI NOMOR 24/PUU-XV/2017 - Ahmad Gelora Mahardika; Mizza Faridatul Anifah (Legacy: Jurnal Hukum dan Perundang-Undangan, 2021)
The verdict of the Constitutional Court Number 24 / PUU-XV / 2017 which rejects the petition for judicial review Article 33 of Law Number 2 Year 2011 on Amendments to Law Number 2 of 2008 on Political Parties presents problems in the Indonesian constitutional system. The Constitutional Court as a constitution escort institution is seen as justifying the actions of the government that interpret the norms in this law subjectively. The ambiguity of this article causes the Government to be reluctant to execute court decisions that have permanent legal force. Indirectly, that’s decision make Djan Faridz's constitutional rights lost. This is because even though there have been several court decisions that have permanent legal force (inkracht van gewisjde), Djan Fraidz still has not received approval from the government. This condition is due to the Minister of Law and Human Rights interpreting subjectively the provisions in Article 33 which regulate internal party political disputes and in the norm stated that the Court's decision is the final decision and there is no dictum requiring the Minister to ratify the results of court decisions.